USABILIDADE ESPACIAL EM UAPS NA CIDADE DE JUIZ DE FORA: ANÁLISE COMPARATIVA DE DOIS CASOS EM 2012 E 2018 - Brandão, Guilherme Valle Loures; Almeida, Caio Augusto Rabite de; Amaral, Wilian Daniel Henriques; Abdalla, José Gustavo Francis (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present paper compares the post-occupation evaluations results realized on two Primary Healthcare Units in Juiz de Fora city MG, between 2012 and 2018, making an integrated walkthrough between the discovery matrix, assessment sheets on comfort and project evaluation sheets. By comparing the results obtained in the studied years, while maintaining the data collection methodology, the perceived incongruity issues relates much more from the buildings aging order and lack of adequate maintenance that of any use related modifications on some spaces. Finally, it is noted that another factor to be considered when comparing the results is the long-term damage perception caused by problems related to the building execution without strict architectural and complementary projects observance, which ultimately generates reflections in the researched buildings usability and useful life.